The Role of the School Committee in Realizing the Strategic Plan at SMAN 1 Tongkuno (Peran Komite Sekolah dalam Mewujudkan Rencana Strategis di SMAN 1 Tongkuno) - Sitti Halima; Muhammad Syarwa Sangila; Badarwan Badarwan (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to describe the role of the school committee in realizing the strategic plan at SMA Negeri 1 Tongkuno. The dimensions that are in the spotlight are: 1) the direction of development of SMAN 1 Tongkuno; 2) The role of the school committee in realizing the strategic plan at SMAN 1 Tongkuno. The research was conducted qualitatively with a descriptive approach, where research data were presented in a narrative manner as a series of systematic and meaningful events. The results show that the direction of development of SMAN 1 Tongkuno is to foster students who have the required scientific capacity, coupled with a relevant curriculum and effective school management, based on strong religious principles. The role of the school committee in realizing the school's strategic plan is carried out in the form of giving consideration, supporting school policies and programs, liaising schools with the community, and carrying out supervision.Keywords: School Committee, Vision and Mission, Strategic Plan, Education QualityPenelitian ini bertujuan untuk mendeskripsikan peran komite sekolah dalam mewujudkan rencana strategis di SMA Negeri 1 Tongkuno. Dimensi yang menjadi sorotan adalah : 1) arah pengembangan SMAN 1 Tongkuno; 2) Peran komite sekolah dalam mewujudkan rencana strategis di SMAN 1 Tongkuno. Penelitian dilakukan secara kualitatif dengan pendekatan deskriptif, dimana data penelitian disajikan secara naratif sebagai rangkaian peristiwa yang sistematik dan memiliki makna. Hasil penelitian menunjukkan bahwa arah pengembangan SMAN 1 Tongkuno adalah pada pembinaan peserta didik yang memiliki kapasitas keilmuan yang dibutuhkan, dibarengi dengan kurikulum yang relevan dan pengelolaan sekolah yang efektif, dilandasi oleh prinsip keagamaan yang kuat. Peran komite sekolah dalam mewujudkan rencana strategis sekolah dijalankan dalam bentuk memberi pertimbangan, mendukung kebijakan dan program sekolah, penghubung sekolah dengan masyarakat, dan melakukan pengawasan.Kata Kunci: Komite Sekolah, Visi dan Misi, Rencana Strategis, Kualitas Pendidikan